Hubungan Sedarah dalam Perspektif Hukum Keluarga Islam - M. Raihan Akbar; Eko Hidayat; Syeh Sarip Hadaiyatullah (Kartika: Jurnal Studi Keislaman, 2026)
Incestuous relationships are prohibited in Islam because they contradict Islamic legal provisions and the principles governing family formation. This prohibition is closely related to the protection of lineage and family honor as part of the objectives of maqāṣid al-sharī'ah. This study aims to analyze incestuous relationships from the perspective of Islamic Family Law and to examine the protection of lineage and family honor in relation to incestuous relationships. This research employs normative legal research with a qualitative approach. The data were obtained through library research, including the Qur'an, Hadith, the Compilation of Islamic Law, legislation, books, scientific journals, and relevant previous studies. The findings indicate that incestuous relationships are prohibited in Islamic Family Law because they contradict Islamic legal provisions and the principles of protecting lineage and family honor. This prohibition also demonstrates the importance of maintaining the boundaries of mahram relationships and order within family life. Therefore, the application of maqāṣid al-sharī'ah, particularly ḥifẓ al-nasl and ḥifẓ al-'ird, is essential in protecting lineage, dignity, and the continuity of the family.